Characterization of mechanical properties of soft tissues using sub-microscale tensile testing and 3D-Printed sample holder. (February 2023) - Kang, John S.; Navindaran, Kishev; Phillips, J.; Kenny, K.; Moon, Kee S.
Abstract: Obtaining the mechanical properties of soft tissues is critical in many medical fields, such as regenerative medicine and surgical simulation training. Although various tissue-characterization methods have been developed, such as AFM, indentation, and elastography, there remain some limitations on their accuracy and validity for measuring small and fragile soft tissues. This paper presents a tensile testing technique to measure the mechanical properties of soft tissues directly and accurately. Tensile testing was chosen as the primary method because of its simple procedure and ability to derive mechanical properties without requiring many assumptions or complicated models. However, tensile testing on soft tissues presents challenges related to gripping the tissue sample without affecting its inherent properties, applying minuscule forces to the sample, and measuring the cross-section area and strain of the sample. To solve these issues, this study presents a sub-micro scale tensile testing system that uses a flexure mechanism and a novel 3D-printed sample holder for gripping the tissue samples. The system also measures tested samples' cross-section area and strain using two high-resolution cameras. The system was validated by testing standard materials and used to characterize the elastic modulus, yield stress, and yield strain of lung tissue slices from six different mice. The results from the validation tests showed a less than 2.5% error for elastic modulus values measured using the tensile tester. At the same time, results from the mice lung tissue measurements revealed qualitative findings that closely matched those seen in the literature and displayed low coefficient of variation values, demonstrating the high repeatability of the system.